Influence of vancomycin and meropenem loading on compressive strength of polymethyl methacrylate bone cement - Popovska, Danica; Avramov, Nikola; Samardjiski, Milan; Shabani, Ilir; Andonovski, Alan; Bogojevska Doksevska, Milena; Stojmenski, Slavcho (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, Co-publisher Scientific foundation Spiroski, 2025)
The rise of antibiotic resistance of certain bacteria to commonly used agents in antibiotic- loaded polymethyl methacrylate (PMMA) bone cement has led to the search for new antibiotic agents. A potential problem in introducing new antibiotics into the PMMA mixture is disruption of the mechanical properties of bone cement, which is intended for mechanical fixation of joint implants. The aim of this study was to test compressive strength of bone cement loaded with vancomycin, meropenem or their combination. Materials and methods: Five groups of samples (PMMA, PMMA+2.5%w/w vancomycin, PMMA+2.5%w/w meropenem, PMMA+1.25%w/w vancomycin and 1.25%w/w meropenem and PMMA+2.5%w/w vancomycin and 2.5%w/w meropenem) were prepared and tested for compressive strength according to specifications of the ISO5833:2002 international standard. Results: All tested groups had compressive strength significantly above the minimum value of 70 MPa set by the standard (87.9 – 98.6MPa, p<.0001). All groups of antibiotic-loaded bone cement had significantly lower compressive strength than PMMA. Conclusion: All tested groups met the basic compressive strength criteria for clinical use in arthroplasty procedures.
Keywords: antibiotic-loaded bone cement; meropenem; vancomycin; compressive strength